Structural analysis of char by Raman spectroscopy: Improving band assignments through computational calculations from first principles. (April 2016) - Smith, Matthew W.; Dallmeyer, Ian; Johnson, Timothy J.; Brauer, Carolyn S.; McEwen, Jean-Sabin; Espinal, Juan F.; Garcia-Perez, Manuel
Abstract: The complex heterogeneous nature of chars has confounded the complete analysis of the Raman spectra of these materials. The additional shoulders observed on the defect (D)-band and high intensity valley between the D and graphitic (G)-bands represent the primary regions of uncertainty. In this paper the effects of various vacancy and substitution defects in a coronene parent molecule have been systematically analyzed using density functional theory (DFT). The impacts of these defects are best understood in terms of a reduced symmetry as compared to a "parent" coronene molecule. Based on simulation results, a total of ten potential bands have been assigned between 1000 cm −1 and 1800 cm −1 . These bands have been used to deconvolute a thermoseries of cellulose chars produced by pyrolysis at 300–700 °C. The shoulder observed in chars near 1200 cm −1 has been assigned to the symmetric breathing mode of various small polyaromatic hydrocarbons (PAH) as well as rings containing seven or more carbons. Intensity between 1400 cm −1 and 1550 cm −1 results from a range of coupled vibrational modes from various defect structures. The deconvolution of cellulose derived chars shows consistent growth of PAH clusters, loss of oxygen, and development of non-hexoganal ring systems as pyrolysis temperature increased.